Strategi Kepemimpinan Kolaboratif Pasmar 1 dalam Penanggulangan Bencana Banjir di Wilayah Jakarta dan Bekasi pada Perspektif Ketahanan Nasional - Ichsan, Andi; Harsono, Gentio; Subiantoro, Yudi (Syntax Literate, 2025)
Pasmar 1 has a significant role in flood disaster management through collaboration with various agencies such as the National Disaster Management Agency (BNPB). However, its implementation still faces several obstacles, particularly related to inter-agency coordination. This study aims to analyze the collaborative leadership model implemented by Pasmar 1 in integrated joint operations for flood disaster management in the Jakarta and Bekasi areas, analyze the obstacles that arise in this collaborative leadership in increasing the success of the operation, and formulate strategic recommendations to strengthen the effectiveness of Pasmar 1's collaborative leadership in future emergency response operations. The research method uses a qualitative, descriptive, and analytical approach. The research subjects included six members of the leadership, the National Disaster Management Agency (BNPB), and the Jakarta and Bekasi regional governments. Data were collected through interviews and analyzed using qualitative descriptive analysis techniques. The results showed that the collaborative leadership model of Pasmar 1 in flood management operations was realized through the active involvement of all stakeholders, effective dialogue, the sustainability of long-term coordination processes, and the guarantee of equal roles and rights between institutions. Barriers identified included limited coordination and communication between institutions, technical and geographical constraints in the field, a command structure that tends to be hierarchical, limited resources and logistics, and differences in perceptions regarding roles and responsibilities between institutions. Strategies to improve the effectiveness of collaborative leadership include strengthening cross-sector human resource capacity, digitizing command and coordination systems, institutionalizing a collaborative culture, improving organizational evaluation and learning, and strengthening the role of commanders as transformational leaders.